Effect Of Liquid Organic Fertilizer Kirinyuh (Chromolaena odorata) On Growth And Production Of Green Palm (Brassica juncea L.) - Eunike Likuayang; Pemmy Tumewu; Langimanapa S. Demmasabu (Jurnal Agroekoteknologi Terapan, 2023)
The research was carried out in the village of Ranoketang Atas, sub-district. Touluaan, district. Southeast Minahasa which took place on August 11 to October 5, 2021. The study used a factorial completely randomized design (CRD) with factor I being the concentration of liquid organic fertilizer kirinyuh (A) which consisted of 3 treatment levels A1 = liquid organic fertilizel kirinyuh 100 ml /liter of water, A2 = liquid organic fertilizel kirinyuh 150 ml/liter of water, A3 = liquid organic fertilizel kirinyuh 200 ml/liter of water and Factor II is the time of administration of liquid organic fertilizel kirinyuh (B), which consists of 3 levels: B1 = 7 days after transplanting, B2 = 7 and 14 days after transplanting, B3 = 7, 14, 21 days after transplanting. Each treatment was repeated 3 times to obtain 27 experimental units. The variables observed were the increase in plant height and number of leaves at the age of 28 and 56 days after transplanting of mustard greens, leaf length, leaf width, and fresh weight of mustard plants observed at harvest. The results showed that there was no interaction between concentration and time of application of organic fertilizer liquid kirinyuh on all observed variables. The single concentration of kirinyuh liquid organic fertilizer had no effect on the increase in plant height, the addition of organic fertilizer had an effect on the increase in the number of mustard leaves. concentration of kirinyuh 150 ml/liter of water was the best for increasing the number of mustard leaves. Keywords : Green Mustard Plant. POC Kirinyuh. Abstrak Penelitian dilaksanakan di desa Ranoketang Atas, kecamatan. Touluaan, kabupaten. Minahasa tenggara yang berlangsung pada 11 Agustus sampai dengan 5 Oktober 2021. Penelitian menggunakan Rancangan Acak Lengkap (RAL) pola faktorial dengan faktor I adalah konsentrasi pupuk organik cair (POC) kirinyuh (A) yang terdiri dari 3 taraf perlakuan A1 = POC Kirinyuh 100 ml/liter air, A2 = POC Kirinyuh 150 ml/liter air, A3 = POC Kirinyuh 200 ml/liter air dan Faktor II adalah waktu pemberian POC Kirinyuh (B), yang terdiri dari 3 taraf : B1 = 7 hari setelah pindah tanam, B2 = 7 dan 14 hari setelah pindah tanam, B3 = 7, 14, 21 hari setelah pindah tanam. Setiap perlakuan  diulangi sebanyak 3 kali sehingga diperoleh 27 satuan percobaan. Variabel yang diamati adalah Pertambahan tinggi tanaman dan pertambahan jumlah daun pada umur 28 dan 56 hari setelah pindah tanam  (HSPT) sawi, panjang daun, lebar daun, dan berat segar tanaman sawi diamati saat panen. Hasil penelitian menunjukkan bahwa tidak terdapat interaksi antara konsentrasi dan waktu pemberian pupuk organik cari kirinyuh terhadap semua variabel yang diamati. Secara tunggal konsentrasi pupuk organik cair kirinyuh tidak berpengaruh pada pertambahan tinggi tanaman, pemberian pupuk organik berpengaruh pada pertambahan jumlah daun sawi. Konsentrasi POC kirinyuh 150 ml/Liter air terbaik pada pertambahan jumlah daun tanaman sawi. Kata kunci : Tanaman Sawi Hijau. POC Kirinyuh.